Nanodiamond particles/reduced graphene oxide composites as efficient supercapacitor electrodes - Wang, Qi; Plylahan, Nareerat; Shelke, Manjusha V.; Devarapalli, Rami Reddy; Li, Musen; Subramanian, Palaniappan; Djenizian, Thierry; Boukherroub, Rabah; Szunerits, Sabine (Carbon, 2014)
The paper reports on the preparation of reduced graphene oxide (rGO) modified with nanodiamond particles composites by a simple solution phase and their use as efficient electrode in electrochemical supercapacitors. The technique relies on heating aqueous solutions of graphene oxide (GO) and nanodiamond particles (NDs) at different ratios at 100 degrees C for 48 h. The morphological properties, chemical composition and electrochemical behavior of the resulting rGO/NDs nanocomposites were investigated using UV/vis spectrometry, Fourier transform infrared (FTIR) spectroscopy, Raman spectroscopy, transmission electron microscopy (TEM) and electrochemical means. The electrochemical performance, including the capacitive behavior of the rGO/NDs composites were investigated by cyclic voltammetry and galvanostatic charge/discharge curves at 1 and 2 A g(-1) in 1 M H2SO4. The rGO/ND matrix with 10/1 ratio displayed the best performance with a specific capacitance of 186 +/- 10 F g (-1) and excellent cycling stability. (C) 2013 Elsevier Ltd. All rights reserved.

Selective isolation and eradication of E. coli associated with urinary tract infections using anti-fimbrial modified magnetic reduced graphene oxide nanoheaters - Halouane, Fatima; Jijie, Roxana; Meziane, Dalila; Li, Chengnan; Singh, Santosh K.; Bouckaert, Julie; Jurazek, Jean; Kurungot, Sreekumar; Barras, Alexandre; Li, Musen; Boukherroub, Rabah; Szunerits, Sabine (Journal of Materials Chemistry B, 2017)
The fast and efficient elimination of pathogenic bacteria from water, food or biological samples such as blood remains a challenging task. Magnetic isolation of bacteria from complex media holds particular promise for water disinfection and other biotechnological applications employing bacteria. When it comes to infectious diseases such as urinary tract infections, the selective removal of the pathogenic species in complex media such as human serum is also of importance. This issue can only be accomplished by adding pathogen specific targeting sites onto the magnetic nanostructures. In this work, we investigate the potential of 2-nitrodopamine modified magnetic particles anchored on reduced graphene oxide (rGO) nanocomposites for rapid capture and efficient elimination of E. coli associated with urinary tract infections (UTIs) from water and serum samples. An optimized magnetic nanocarrier achieves a 99.9% capture efficiency even at E. coli concentrations of 1 x 10(1) cfu mL(-1) in 30 min. In addition, functionalization of the nanostructures with poly(ethylene glycol) modified pyrene units and anti-fimbrial E. coli antibodies allowed specific elimination of E. coli UTI89 from serum samples. Irradiation of the E. coli loaded nanocomposite with a near-infrared laser results in the total ablation of the captured pathogens. This method can be flexibly modified for any other pathogenic bacteria, depending on the antibodies used, and might be an interesting alternative material for a magnetic-based body fluid purification approach.